Bacterial Community Succession, Transmigration, and Differential Gene Transcription in a Controlled Vertebrate Decomposition Model - Burcham, Zachary M.; Pechal, Jennifer L.; Schmidt, Carl J.; Bose, Jeffrey L.; Rosch, Jason W.; Benbow, M. Eric; Jordan, Heather R. (Frontiers in Microbiology, 2019)
Decomposing remains are a nutrient-rich ecosystem undergoing constant change due to cell breakdown and abiotic fluxes, such as pH level and oxygen availability. These environmental fluxes affect bacterial communities who respond in a predictive manner associated with the time since organismal death, or the postmortem interval. Profiles of microbial taxonomic turnover and transmigration are currently being studied in decomposition ecology, and in the field of forensic microbiology as indicators of the postmortem interval. We monitored bacterial community structural and functional changes taking place during decomposition of the intestines, bone marrow, lungs, and heart in a highly controlled murine model. We found that organs presumed to be sterile during life are colonized by Clostridium during later decomposition as the fluids from internal organs begin to emulsify within the body cavity. During colonization of previously sterile sites, gene transcripts for multiple metabolism pathways were highly abundant, while transcripts associated with stress response and dormancy increased as decomposition progressed. We found our model strengthens known bacterial taxonomic succession data after host death. This study is one of the first to provide data of expressed bacterial community genes, alongside transmigration and structural changes of microbial species during laboratory controlled vertebrate decomposition. This is an important dataset for studying the effects of the environment on bacterial communities in an effort to determine which bacterial species and which bacterial functional pathways, such as amino acid metabolism, provide key changes during stages of decomposition that relate to the postmortem interval. Finding unique postmortem interval species or functions can be useful for determining time since death in forensic investigations.